Induction of apoptosis in melanoma A375 cells by a chloroform fraction of Centratherum anthelminticum (L.) seeds involves NF-kappaB, p53 and Bcl-2-controlled mitochondrial signaling pathways - Looi, C.Y.; Moharram, B.; Paydar, M.; Wong, Y.L.; Leong, K.H.; Mohamad, K.; Arya, A.; Wong, W.F.; Mustafa, Mohd Rais (BioMed Central, 2013)
Background: Centratherum anthelminticum (L.) Kuntze (scientific synonyms: Vernonia anthelmintica; black cumin) is one of the ingredients of an Ayurvedic preparation, called Kayakalpâ, commonly applied to treat skin disorders in India and Southeast Asia. Despite its well known anti-inflammatory property on skin diseases, the anti-cancer effect of C. anthelminticum seeds on skin cancer is less documented. The present study aims to investigate the anti-cancer effect of Centratherum anthelminticum (L.) seeds chloroform fraction (CACF) on human melanoma cells and to elucidate the molecular mechanism involved. Methods: A chloroform fraction was extracted from C. anthelminticum (CACF). Bioactive compounds of the CACF were analyzed by liquid chromatography-tandem mass spectrometry (LC-MS/MS). Human melanoma cell line A375 was treated with CACF in vitro. Effects of CACF on growth inhibition, morphology, stress and survival of the cell were examined with MTT, high content screening (HSC) array scan and flow cytometry analyses. Involvement of intrinsic or extrinsic pathways in the CACF-induced A375 cell death mechanism was examined using a caspase luminescence assay. The results were further verified with different caspase inhibitors. In addition, Western blot analysis was performed to elucidate the changes in apoptosis-associated molecules. Finally, the effect of CACF on the NF-ÎºB nuclear translocation ability was assayed. Results: The MTT assay showed that CACF dose-dependently inhibited cell growth of A375, while exerted less cytotoxic effect on normal primary epithelial melanocytes. We demonstrated that CACF induced cell growth inhibition through apoptosis, as evidenced by cell shrinkage, increased annexin V staining and formation of membrane blebs. CACF treatment also resulted in higher reactive oxygen species (ROS) production and lower Bcl-2 expression, leading to decrease mitochondrial membrane potential (MMP). Disruption of the MMP facilitated the release of mitochondrial cytochrome c, which activates caspase-9 and downstream caspase-3/7, resulting in DNA fragmentation and up-regulation of p53 in melanoma cells. Moreover, CACF prevented TNF-Î±-induced NF-ÎºB nuclear translocation, which further committed A375 cells toward apoptosis. Conclusions: Together, our findings suggest CACF as a potential therapeutic agent against human melanoma malignancy.